PREGNANCY OUTCOME FOLLOWING IVF CAN BE PREDICTED BY A GENE EXPRESSION SIGNATURE IN HUMAN CUMULUS CELLS. - Iager, A. E.; Kocabas, A. M.; Otu, H. H.; Fernandez, E.; Cibelli, J. B.; Crosby, J. A. (Elsevier Science Inc, 2012)
[Abstract Not Available]
68th Annual Meeting of the American-Society-for-Reproductive-Medicine (ASRM) -- OCT 20-24, 2012 -- San Diego, CA